Pengaruh Perubahan Kurs Valuta Asing (Nilai Tukar Rupiah) dan Tingkat Inflasi Terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI): Sebuah Studi Literatur - Sifa, Anida Aulia (PT Hakhara Akademia Indonesia, 2024)
This research aims to present a review and analysis of the influence of changes in foreign exchange rates (rupiah exchange rate) and inflation rates on share prices of banking companies listed on the Indonesia Stock Exchange (BEI). The problem in this journal review is whether changes in foreign exchange rates and inflation rates can affect banking share prices. The research results show that changes in foreign exchange rates and inflation rates significantly influence banking company share prices. Fluctuations in foreign exchange rates and high inflation rates can increase uncertainty for investors, thereby impacting their investment decisions.